2022
DOI: 10.1371/journal.pone.0272023
|View full text |Cite
|
Sign up to set email alerts
|

A novel endocast technique providing a 3D quantitative analysis of the gastrovascular system in Rhizostoma pulmo: An unexpected through-gut in cnidaria

Abstract: The investigation of jellyfish gastrovascular systems mainly focused on stain injections and dissections, negatively affected by thickness and opacity of the mesoglea. Therefore, descriptions are incomplete and data about tridimensional structures are scarce. In this work, morphological and functional anatomy of the gastrovascular system of Rhizostoma pulmo (Macri 1778) was investigated in detail with innovative techniques: resin endocasts and 3D X-ray computed microtomography. The gastrovascular system consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Section III showed that the existing literature (Nielsen, 1987) has neglected the presence of cilia in cnidarians. However, we found evidence for the presence of a ciliated epidermis within Cnidaria (with the exception of Myxozoa; Canning & Okamura, 2004), with examples in Anthozoa (Wainwright & Koehl, 1976; Chia & Crawford, 1977; Shapiro et al ., 2014), Hydrozoa (Mackie et al ., 1989; Colin et al ., 2005), Cubozoa (Golz & Thurm, 1993), Staurozoa (Larson, 1980; Dawson & Hamner, 2009; Miranda et al ., 2016), and Scyphozoa (Smith, 1936; Southward, 1949, 1955; Chia et al ., 1984a; Heeger & Möller, 1987; Larson, 1987, 1997; Nagata et al ., 2016; Turk et al ., 2021; Avian et al ., 2022). The presence of this epidermis and its specific functions in the different taxa are little known and often neglected.…”
Section: Feeding Phases In Medusaementioning
confidence: 99%
“…Section III showed that the existing literature (Nielsen, 1987) has neglected the presence of cilia in cnidarians. However, we found evidence for the presence of a ciliated epidermis within Cnidaria (with the exception of Myxozoa; Canning & Okamura, 2004), with examples in Anthozoa (Wainwright & Koehl, 1976; Chia & Crawford, 1977; Shapiro et al ., 2014), Hydrozoa (Mackie et al ., 1989; Colin et al ., 2005), Cubozoa (Golz & Thurm, 1993), Staurozoa (Larson, 1980; Dawson & Hamner, 2009; Miranda et al ., 2016), and Scyphozoa (Smith, 1936; Southward, 1949, 1955; Chia et al ., 1984a; Heeger & Möller, 1987; Larson, 1987, 1997; Nagata et al ., 2016; Turk et al ., 2021; Avian et al ., 2022). The presence of this epidermis and its specific functions in the different taxa are little known and often neglected.…”
Section: Feeding Phases In Medusaementioning
confidence: 99%